2004
DOI: 10.1149/1.1763141
|View full text |Cite
|
Sign up to set email alerts
|

Solvated Li-Ion Transfer at Interface Between Graphite and Electrolyte

Abstract: Solvated lithium-ion transfer at the interface between the graphite and electrolyte was investigated by ac impedance spectroscopy. Electrolytes consisting of 1 mol dm−3 LiCF3SO3 dissolved in 1,2-dimethoxyethane (DME) and dimethylsulfoxide (DMSO) were used. Cyclic voltammograms of highly oriented pyrolytic graphite in the above electrolytes showed that solvated lithium ion intercalation occurred below a potential of 1.5 V (vs. normalLi/Li+false). In 1 mol dm−3 LiCF3SO3/DME electrolyte, impedance spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
447
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 544 publications
(491 citation statements)
references
References 19 publications
41
447
3
Order By: Relevance
“…In general, metal deposition in liquid electrolytes contains electron transfer from an electrode to metal ion and the following desolvation or solvent reorganization. Abe et al 16 and Uchimoto et al 17 suggested that Li/Li + couple reactions at the electrode/electrolyte interface in various organic electrolyte soutions had high activation barrier which was strongly influenced by the solvation and desolvation of Li ions. These strongly suggest that for the Li deposition in the present liquid electrolyte the desolvation step after electron transfer from the electrode to Li + ion is rate-determining.…”
Section: Resultsmentioning
confidence: 99%
“…In general, metal deposition in liquid electrolytes contains electron transfer from an electrode to metal ion and the following desolvation or solvent reorganization. Abe et al 16 and Uchimoto et al 17 suggested that Li/Li + couple reactions at the electrode/electrolyte interface in various organic electrolyte soutions had high activation barrier which was strongly influenced by the solvation and desolvation of Li ions. These strongly suggest that for the Li deposition in the present liquid electrolyte the desolvation step after electron transfer from the electrode to Li + ion is rate-determining.…”
Section: Resultsmentioning
confidence: 99%
“…However, which step or steps are rate determining cannot be differentiated using this method. The results from Ogumi's group reasonably concluded that the desolvation is the predominant limiting step in the Li + charge transfer across the electrolyte/electrode interface [7][8] . This study provides a different perspective by studying the anode and the cathode in the same electrolyte at the same time.…”
Section: Activation Energy Of Graphitic Carbon Anode and Lithium Mixementioning
confidence: 99%
“…Due to this manner of interphasial species accumulating on a simple surface, this formation mechanism was often referred to as "2D formation model" of SEI. It must be More recent studies by Abe et al identified this desolvation process at electrode/electrolyte interphase as the "rate determining step" in the operation of a Li ion device, which is largely responsible for the cell resistance at low temperature or under high drain rate applications [23,24]. An issue of particular interest concerns how bulk electrolyte composition affects the chemical ingredients of SEI.…”
Section: Chemistry and Formation Mechanism Of Seimentioning
confidence: 99%